Spectrophotometric Determination of Lercanidipine in Pharmaceutical Formulations - Vijaya Saradhi, S.; Himabindu, V.; Devala Rao, G. (Asian Journal of Chemistry, 2010)
A simple and sensitive spectrophotometric method is developed for the determination of lercanidipine in bulk and in pharmaceutical formulations. The method is based on diazotization of reduced lercanidipine followed by addition of ammonia solution. The absorbance of the yellow colour solution developed was measured at 445 nm. Beer's law is obeyed in the concentration range of 5–25 μg/mL. Results of analysis were validated statistically and by recovery studies. The method is successfully employed for the determination of Lercanidipine in various pharmaceutical preparations.